North Korea's second nuclear crisis and northeast Asian security - Joo, Seung-Ho 1959-; Kwak, Tae-Hwan 1938- (Ashgate, 2007)
This key volume provides in-depth analysis of the inter-Korean and international dynamics of North Korea's nuclear crisis. It offers new insights into the six-party talks designed to resolve the crisis, suggests creative formulas to resolve the ongoing crisis and delves into the interests and policies of the major powers at the six-party negotiating table.